A systematic review and meta-analysis of hybrid aortic arch replacement - Moulakakis, Konstantinos G.; Mylonas, Spyridon N.; Markatis, Fotis; Kotsis, Thomas; Kakisis, John; Liapis, Christos D. (Annals of Cardiothoracic Surgery; Vol 2, No 3 (May 30, 2013): Aortic arch surgery (II), 2013)
Background: Evolution in the endovascular era has influenced the management of aortic arch pathologies. Several studies have described the use of a combined endovascular and open surgical approach to the treatment of arch diseases. Hybrid repair of arch pathologies has been considered as a less invasive method, and is therefore an appealing option for high-risk patients who are unsuitable for open repairs. The aim of the present meta-analysis was to assess the efficacy of hybrid techniques in patients with aortic arch pathologies. Methods: Extensive electronic literature search was undertaken to identify all articles published up to December 2012 that described hybrid aortic arch repair with intrathoracic supra-aortic branch revascularisation and subsequent stent graft deployment. Eligible studies were divided into two groups: group I included studies on the aortic arch debranching procedure and group II included studies that reported an elephant trunk technique (either “frozen” or stented). Separate meta-analyses were conducted in order to assess technical success, stroke, spinal cord ischemia (SCI), renal failure requiring dialysis, and cardiac and pulmonary complications rate, as well as 30-day/in-hospital mortality. Results: Forty-six studies were eligible for the present meta-analysis: 26 studies with a total of 956 patients reported aortic arch debranching procedures, and 20 studies with 1,316 patients performed either ‘frozen’ or stented elephant trunk technique. The pooled estimate for 30-day/in-hospital mortality was 11.9% for the arch debranching group and 9.5% for the elephant trunk group. Cerebrovascular events of any severity were found to have occurred postoperatively at a pooled rate of 7.6% and 6.2%, while irreversible spinal cord injury symptoms were present in a pooled estimate of 3.6% and 5.0% in the arch debranching and elephant trunk group, respectively. Renal failure requiring dialysis occurred at 5.7% and 3.8% in both groups, while cardiac complications rate was 6.0% in the arch debranching cohort and pulmonary complication was 19.7% in the elephant trunk cohort. Conclusions: Hybrid arch techniques provide a safe alternative to open repair with acceptable short- and mid-term results. However, stroke and mortality rates remain noteworthy. Future prospective trials that compare open conventional techniques with the hybrid method or the entirely endovascular methods are needed.